ANALISIS NILAI MORAL AGAMA DALAM SYAIR GURU SYUKUR TERUSAN JAMBI - Ahmad Hariandi; Suci Dewi Asmara; Sinta Nofria; Arini Meliza; Ida Fransiska Lingga (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
This research aims to know the meaning and moral contained in the poetry of Haji Syukur. He conveyed his preaching through poetry that according to Haji Syukur, the people of Jambi easily understand him through Seloko or Pantun. The poems spoken by Haji Syukur are also often used by people in the area of Jambi who in the activities of community deliberations, in giving advice, can also be used in the sleep of children, and storytelling. The poems spoken by Haji Syukur contain the story of Islamic religious teachings.Further research on the activity of analyzing the works of the teacher H. Syukur specifically the poems of his work.In this study we use content analysis techniques to process the data that has been collected. With this technique researchers will be able to easily find out the contents, meaning of poetry, and moral values that are embedded in poetry. So that researchers at the end of the paper can easily conclude the results of the desired research.The words of Haji Syukur or the often-called Guru Syukur in the form of aspects are also not too difficult to understand, the lyrics are practical and often also used by society in their daily lives, and Seloko or Pantun is also a Community needs in certain events and when people relax in a community gathering. In the Haji Syukur poem’s can also distinguish the nature of the character of Islam with the people of the calamites, the good and the wicked, the praises and the Unblemish. In the verses of gratitude teachers speak between two opposite things, Haji Syukur also gives the difference two things aloud, so that the community easier to capture what the meaning conveyed through the poem and the the lyrics are easier for the community to hear.